REIMAGINING EDUCATION IN THE DIGITAL AGE: THEORETICAL FOUNDATIONS AND BEST PRACTICES IN LEARNER-CENTERED PEDAGOGY - Sojida Umirzakovna Allayarova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This paper explores the evolution and impact of digital pedagogy and learner-centered education in the context of 21st-century technological transformation. Drawing on key theoretical frameworks such as humanism, social constructivism, and connectivism, it examines the philosophical and practical shifts that have reshaped educational paradigms. The role of digital technologies is analyzed not just as tools for instruction but as catalysts for systemic change in teaching and learning. The paper further discusses the importance of developing a coherent digital pedagogy, identifying tools and best practices that align with learner autonomy, creativity, and collaboration. Through the lens of critical pedagogy, the study highlights the challenges and opportunities educators face when integrating digital tools in classrooms and designing transformative learning environments.